CPT1A mediates the succinylation of SP5 which activates transcription of PDPK1 to promote the viability and glycolysis of prostate cancer cells - Shufeng Liu; Xiaoguang Chen; Liqi Zhang; Bo Lu (Cancer Biology & Therapy)
Succinylation modification involves in the progression of human cancers. The present study aimed to investigate the role of CPT1A, which is a succinyltransferase in the progression of prostate cancer (PCa). CCK-8 was used to detect the cell viability. Seahorse was performed to evaluate the cell glycolysis. Luciferase assay was used to detect the transcriptional regulation. ChIP was performed to assess the binding between transcriptional factors with the promoters. Co-IP was used to assess the binding between proteins. We found that CPT1A was highly expressed in PCa tissues and cell lines. Silencing of CPT1A inhibited the viability and glycolysis of PCa cells. Mechanistically, CPT1A promoted the succinylation of SP5, which strengthened the binding between SP5 and the promoter of PDPK1. SP5 activated PDPK1 transcription and PDPK1 activated the AKT/mTOR signal pathway. These findings might provide novel targets for the diagnosis or therapy of prostate cancer.